Evaluation of choroidal thickness in prodromal Alzheimer’s disease defined by amyloid PET - López-de-Eguileta, Alicia; Lage, Carmen; López-García, Sara; Pozueta, Ana; García-Martínez, María; Kazimierczak, Martha; Bravo, María; de Arcocha-Torres, María; Banzo, Ignacio; Jimenez-Bonilla, Julio; Cerveró, Andrea; Goikoetxea, Alexander; et al. (PloS one, 2020)
To assess and compare the involvement of choroidal thickness (CT) in patients with mild cognitive impairment (MCI) and dementia due to Alzheimer's disease (AD) defined by amyloid PET and healthy controls (HC). Sixty-three eyes from 34 AD patients [12 eyes (19.0%) with dementia and 51 eyes (80.9%) with MCI], positive to .sup.11 C-labelled Pittsburgh Compound-B with positron emission tomography (.sup.11 C-PiB PET/CT), and the same number of sex- and age-paired HC were recruited. All participants underwent enhanced depth imaging optical coherence tomography (EDI-OCT) assessing CT at 14 measurements from 2 B-scans. Paired Student t-test was used to compare CT measurements between MCI, dementia and sex- and age-paired HC. A univariate generalized estimating equations model (GEE) test was performed to compare MCI and dementia individually with all HC included. Compared with HC, eyes from patients with positive .sup.11 C-PiB PET/CT showed a significant CT thinning in 5 selected locations (in foveal thickness in vertical scan, in temporal scan at 1500[mu]m, in superior scan at 500[mu]m and in inferior scan at 1000[mu]m and 1500[mu]m, p = 0.020-0.045) whilst few significant CT reduction data was reported in MCI or dementia individually versus HC. However, the GEE test identified significant CT thinning in AD compared with all HC included (p = 0.015-0.046). To our knowledge, the present study is the first measuring CT in eyes from MCI and dementia eyes positive to .sup.11 C-PiB PET/CT reporting a significant trend towards CT thinning in MCI patients which became more pronounced in dementia stage. We support further investigation involving larger and prospective OCT studies in AD population characterized with available biomarkers to describe whether choroidal vascular damage occurs specifically in prodromal stages of AD.